SISTEM INFORMASI TRUECARE CSR TELKOM BERBASIS WEB PADA PT. TELEKOMUNIKASI INDONESIA - Indah Hermina Agustin; Tuti Haryanti (Jurnal Techno Nusa Mandiri, 2015)
TrueCare Information System Web-based Telkom CSR on Service Division PT. Telekomunikasi Indonesia. The results showed the application of Information Systems Customer Service Representative (CSR) to support the company in view of the technological and business concepts that are used to run its business processes through interactions with customers. The interaction that occurs between the customer and the company not only through service of course but also through sales and marketing. In addition, the implementation of CSR Information Systems, supported by information systems and technology infrastructure as supporting its success. Broadly speaking, the application of Information Systems Customer Service Representative (CSR) can members an enhanced service to customers through existing developments, such as the standardization of patterns of Customer Service Representative (CSR), one-stop service, utilization of information systems, and the development of service time due to time efficiency through a number of process automation services.